7-3y=5+4y+11-16y

Simple and best practice solution for 7-3y=5+4y+11-16y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-3y=5+4y+11-16y equation:


Simplifying
7 + -3y = 5 + 4y + 11 + -16y

Reorder the terms:
7 + -3y = 5 + 11 + 4y + -16y

Combine like terms: 5 + 11 = 16
7 + -3y = 16 + 4y + -16y

Combine like terms: 4y + -16y = -12y
7 + -3y = 16 + -12y

Solving
7 + -3y = 16 + -12y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '12y' to each side of the equation.
7 + -3y + 12y = 16 + -12y + 12y

Combine like terms: -3y + 12y = 9y
7 + 9y = 16 + -12y + 12y

Combine like terms: -12y + 12y = 0
7 + 9y = 16 + 0
7 + 9y = 16

Add '-7' to each side of the equation.
7 + -7 + 9y = 16 + -7

Combine like terms: 7 + -7 = 0
0 + 9y = 16 + -7
9y = 16 + -7

Combine like terms: 16 + -7 = 9
9y = 9

Divide each side by '9'.
y = 1

Simplifying
y = 1

See similar equations:

| 2(x-x-5+2)=6 | | 6x^2+16x-20=0 | | -0.75-x=0.5 | | 4t+9=-8t+13 | | 4x^2-19x+23=-2x+8 | | 8j=69 | | x^2-x-6=3x-1 | | 8-(-9)=1 | | (2x+5)(x-6)=0 | | x^2+12+33=6 | | 3ax-2bx+7=21+x | | 9x^2-0.3x=0 | | M=450-180 | | 12+3x-14.2=x+5.8-3x | | 5+3x=65-3x | | ax-2=4x+a | | 5-(2x-4)=x | | 5x+5=4x-4 | | 3y+5=7y+4 | | 3y+5=7g+4 | | n^2-n-180=0 | | 2x+49=9x-5 | | 7x-5=10(3) | | 12-3(x+2)=x+8 | | 2a-1b=200 | | 21y-2=9 | | 3x+5=-29-8x | | x^2-66x+216=0 | | 15y-10-8+6y=9 | | 15x-10-8+6y=9 | | 2x-2=10-50 | | 2y-5y=17solvey |

Equations solver categories